Working capital management and its impact on financial performance: an analysis of trading firms - Yogendrarajah, R.; Thanabalasingam, S. (Proceedings in the International Conference on Modern Trends in Innovative Management (MTIM) at Rajarata University., 2011)
A Working capital management ensures a company has sufficient cash flow in order to meet its short-term debt obligations and operating expenses. The needs of efficient working capital management must be considered in relation to other aspects of the firms’ financial and non-financial performance. An efficient Working Capital Management is expected to contribute to the high financial performance. The main purpose of this study was to investigate the working capital management and its impact on firms’ financial performance. The efficiency of working capital management was investigated through the cash conversion cycle. The research problem focused here ―What extent the working capital management influences on financial performance of the trading firms?‖ A strong significant relationship between working capital management and profitability has been identified in previous research. It was assumed that ―The efficient working capital management has strong impact on financial performance‖. The dependent variable Return on Assets is used as a measure of profitability of financial performance and its’ relationship with working capital management was investigated to find out the results. Samples of 9 trading firms have been selected from the companies listed by the Colombo stock exchange using Statistical Package for Social Sciences (SPSS) for the period of 2004 to 2009 to find out the results. The regression analysis results show that the high investment in inventories and receivables is associated with lower financial performance (ROA). For this analysis the inventories days, accounts receivable days, accounts payable days and cash operating cycle have been used. The findings also revealed that some firms have efficient working capital management and some have inefficient working capital management in the trends of working capital according to the cash operating cycle.
Keywords: Working Capital management; Financial performance; Accounts receivable; Accounts payable; Cash operating cycle